Formal synthesis of pinolide via L-proline-catalyzed sequential alpha-aminooxylation, horner-wadsworth-emmons olefination and sharpless asymmetric dihydroxylation - Shelke, Anil M.; Suryavanshi, Gurunath (Tetrahedron-Asymmetry, 2016)
A convergent, formal enantioselective synthesis of pinolide, a new nonenolide, has been achieved with high enantiomeric purity (99% ee) starting from readily available raw materials. The main highlight of the synthetic strategy is the application of L-proline catalyzed sequential alpha-aminooxylation and Horner-Wadsworth-Emmons olefination of an aldehyde, Sharpless asymmetric dihydroxylation and Steglich esterification as the key steps for the construction of a key chiral intermediate of the target molecule. (C) 2016 Elsevier Ltd. All rights reserved.